2000
DOI: 10.2337/diabetes.49.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal beta-cell apoptosis: a trigger for autoimmune diabetes?

Abstract: In neonatal rodents, the beta-cell mass undergoes a phase of remodeling that includes a wave of apoptosis. Using both mathematical modeling and histochemical detection methods, we have demonstrated that beta-cell apoptosis is significantly increased in neonates as compared with adult rats, peaking at approximately 2 weeks of age. Other tissues, including the kidney and nervous system, also exhibit neonatal waves of apoptosis, suggesting that this is a normal developmental phenomenon. We have demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
215
1
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(227 citation statements)
references
References 39 publications
9
215
1
2
Order By: Relevance
“…Genetic and environmental factors that affect their responses have been linked to the pathogenesis of DMT1, although the exact mechanisms remain unknown (Fan et al 2004;Shultz et al 1995). It has been suggested that deficient internalization and/or clearance of AC by Mfs may be linked to the development of autoimmunity (O'Brien et al 2006;Trudeau et al 2000;Marée et al 2008;Mohammad et al 2006). Both AC and pathogens are internalized by phagocytosis, although the cell surface receptors involved in these processes are different.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic and environmental factors that affect their responses have been linked to the pathogenesis of DMT1, although the exact mechanisms remain unknown (Fan et al 2004;Shultz et al 1995). It has been suggested that deficient internalization and/or clearance of AC by Mfs may be linked to the development of autoimmunity (O'Brien et al 2006;Trudeau et al 2000;Marée et al 2008;Mohammad et al 2006). Both AC and pathogens are internalized by phagocytosis, although the cell surface receptors involved in these processes are different.…”
Section: Resultsmentioning
confidence: 99%
“…It is well accepted that the initiation and the progression of DMT1 is linked to intrinsic dysfunction in professional phagocytes (i.e., Mfs), which results in a compromised mounting of immune and inflammatory responses (Fan et al 2004;Shultz et al 1995;O'Brien et al 2006;Trudeau et al 2000;Marée et al 2008;Mohammad et al 2006). For example, it has been shown that deficient internalization of AC by Mfs derived from diabetic individuals is accompanied by decreased production of IL-10 and increased secretion of pro-inflammatory cytokines, generating an unusual pro-inflammatory environment in response to AC (O'Brien et al 2006;Trudeau et al 2000;Marée et al 2008;Mohammad et al 2006). On the contrary, incubation of DMT1-derived Mfs with pro-inflammatory stimuli has been shown to produce unusually high levels of PGE 2 , which leads to down-regulation of cellular immune activation and therefore a decrease in inflammation (Benhamou et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Although the notion of early programming of Type 1 diabetes, which underlies this work, has not yet been clearly addressed in the literature, early events such as viral infection (in humans [26]), early induction of high levels of glucocorticoids [27] and a higher wave of apoptosis in islets of neonates (in the non-obese diabetic mouse [28,29]) have been associated with the later development of Type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The second wave of expansion of endocrine cells is noted at day 15 (Han et al, 1986). There is evidence of considerable restructuring of the endocrine pancreas through islet cell apoptosis in neo-nates (Trudeau et al, 2000). The GLP-1R transcript has been detected in rat fetal islets taken at embryonic day 21 and in neonate suckling rats (Garcia-Flores et al, 2001).…”
Section: Effects Of Glp-1r Activation During Pancreatic Development Amentioning
confidence: 99%